2018
DOI: 10.1021/acsanm.8b00219
|View full text |Cite
|
Sign up to set email alerts
|

Polyethylenimine-Modified Graphene Oxide as a Novel Antibacterial Agent and Its Synergistic Effect with Daptomycin for Methicillin-Resistant Staphylococcus aureus

Abstract: An aqueous dispersion of polyethylenimine-modified graphene oxide (PEI-GO) was prepared via a one-step synthesis through an epoxy ring-opening reaction. PEI-GO exhibited bacterial growth inhibition activity on methicillin-resistant Staphylococcus aureus (MRSA) with a minimum inhibitory concentration as low as 8 μg mL–1. Time–kill curve assay and SYTOX Green assay showed the antibacterial activity and bacteria cell membrane permeability of PEI-GO, respectively. Most importantly, when PEI-GO was employed at 1–2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 51 publications
(72 reference statements)
2
21
0
Order By: Relevance
“…Next we tested the combination with tobramycin, finding that GQD had a synergistic effect on the efficiency of tobramycin. This is similar to what has been reported by Fan et al who also found a synergistic effect of polyethyleneimine-graphene oxide on daptomycin in the treatment of Staphylococcus aureus [33]. When we combined VNB pre-treatment of P. aeruginosa biofilms with subsequent addition of tobramycin, a significant effect on biofilm viability was found, confirming that VNB from GQD can enhance the diffusion of tobramycin and enhance its effectivity, similar to what we have shown before with AuNP [10].…”
Section: Discussionsupporting
confidence: 91%
“…Next we tested the combination with tobramycin, finding that GQD had a synergistic effect on the efficiency of tobramycin. This is similar to what has been reported by Fan et al who also found a synergistic effect of polyethyleneimine-graphene oxide on daptomycin in the treatment of Staphylococcus aureus [33]. When we combined VNB pre-treatment of P. aeruginosa biofilms with subsequent addition of tobramycin, a significant effect on biofilm viability was found, confirming that VNB from GQD can enhance the diffusion of tobramycin and enhance its effectivity, similar to what we have shown before with AuNP [10].…”
Section: Discussionsupporting
confidence: 91%
“…indicating the doping effect of N element and quaternary ammonium group in qCQDs 26,38,39 . The high-resolution results of O1s (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The C 1s spectra of GO could be fitted into four fitted curves, which were assigned to C–C (sp 2 and sp 3 ), C–O, C=O, and O=C–O at 284.5, 286.4, 287.2, and 288.8 eV, respectively [ 45 , 46 , 47 ]. In addition, the C 1s spectra of GO-g-PTA-F and GO- g -PTA-A could be fitted into five fitted curves, which were assigned to C–C (sp 2 and sp 3 ), C–O, C=O, O=C–O, and C–N, at 284.5, 286.4, 287.2, 288.8, and 285.6 eV, respectively [ 25 , 48 ]. The relative intensity of the C–N peak of GO- g -PTA-F and GO- g -PTA-A samples significantly increased, and the relative intensity of the C–O peak of GO- g -PTA-F and GO- g -PTA-A samples decreased.…”
Section: Resultsmentioning
confidence: 99%
“…To improve the antimicrobial activity of GO, different types of cationic polymer were added onto GO surface. Fan et al [ 25 ] demonstrated that cationic polymer-modified GO, such as polyethylenimine-modified GO via an epoxy ring opening reaction, showed higher biocidal efficacy than GO at the same concentration.…”
Section: Introductionmentioning
confidence: 99%